Characterization of novel arrhythmogenic patterns arising secondary to heterogeneous expression and activation of Nav1.8 - Zhang, Zhong-He; Barajas-Martinez, Hector; Duan, Hong-Yi; Fan, Guo-Hua; Jiang, Hong; Antzelevitch, Charles; Xia, Hao; Hu, Dan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPrevious studies suggested that SCN10A/Nav1.8 may influence cardiac electrophysiology and the susceptibility to cardiac arrhythmias. Notably, the expression of SCN10A is not uniform, showing variable expression in each cardiac chamber. The present study aims to explore the functional significance of Nav1.8 expression among different cell types present in the ventricular myocardium.MethodsThe effect of the specific Nav1.8 blocker, A-803467, on action potential was recorded from epicardial, mid-myocardial (M cells) and Purkinje tissue slices isolated from the canine left ventricle using standard microelectrode techniques and on late sodium current from Purkinje cells using patch-clamp techniques.ResultsA-803467 treatment did not significantly affect maximum diastolic potential, action potential amplitude or maximum rate of rise of the action potential upstroke in epicardial cells, M cells or Purkinje fibers. Action potential duration (APD) was also unaffected by A-803467 in epicardial cells. However, administration of 1,000 nmol/L A-803467 reduced APD30, APD50, and APD90 during relatively slow pacing rates of 0.2 and 0.5 Hz in M cells. In Purkinje fibers, A-803467 (100 and 1,000 nmol/L) substantially abbreviated APD50 and APD90 at slow pacing rates (0.2 and 0.5 Hz). Moreover, 100 nmol/L A-803467 significantly inhibited the development of early afterdepolarizations induced by 10 nmol/L ATX-II (7/8 vs. 2/8, p < 0.05) as well as the amplitude of late sodium current at 0.2 Hz in Purkinje cells.ConclusionsThe functional significance of Nav1.8 varies among different types of ventricular and conduction system cardiomyocytes. The reduction in INa,L and APD, as well as suppression of early afterdepolarizations by Nav1.8 block in Purkinje fibers suggests Nav1.8 as a potential therapeutic target for bradycardia-dependent arrhythmias.